Control and dynamic competition of bright and dark lasing states in active nanoplasmonic metamaterials - Wuestner, S.; Hamm, J.M.; Pusch, A.; Renn, F.; K. L. Tsakmakidis; Hess, O. (Physical Review B - Condensed Matter and Materials Physics, 2012)
Active nanoplasmonic metamaterials support bright and dark modes that compete for gain. Using a Maxwell-Bloch approach incorporating Langevin noise we study the lasing dynamics in an active nanofishnet structure. We report that lasing of the bright negative-index mode is possible if the higher-Q dark mode is discriminated by gain, spatially or spectrally. The nonlinear competition during the transient phase is followed by steady-state emission where bright and dark modes can coexist. We analyze the influence of pump intensity and polarization and explore methods for mode control. © 2012 American Physical Society.